Association between Characteristics and Behaviors of Workers that Exposed to Chemicals with ARI Symptoms in Artificial Nails Industry - Kurniasih, Oktavera Tri; Aphridasari, Jatu; ., Sumardiyono (Nexus Kedokteran Klinik, 2016)
Background: Artifical nails industry workers are potentially exposed to chemicals that can irritate the respiratory tract. Irritation of the respiratory tract may facilitate the occurrence of Acute Respiratory Infection (ARI). Worker characteristics and worker behaviors affect the occurrence of ARI. This research aimed to know the association between characteristics and behaviors of workers that exposed to chemicals with ARI symptoms in artificial nails industry. Methods: This research was an observational analytic with cross-sectional approach. The research was held in artificial nails industry of Purbalingga on November-December 2015 with 80 samples of workers which consisted of 48 workers of injection department and 32 workers of airbrush department. Independent variables of this research were worker characteristics and worker behaviors. Worker characteristics included gender, age, department of work, period of work, and length of work. Worker behaviors included behavior of the use of Personal Protective Equipment (PPE) such as masks and smoking behavior. Dependent variable of this research was ARI symptoms. Moderator variable of this research was chemicals exposure. Data were collected using questionnaires. Data were analyzed by multiple logistic regression analysis. Results: The results of multiple logistic regression analysis showed that variables that influence ARI symptoms were length of work (p = 0.000; PR = 13.28) and age (p = 0.001; PR = 10.53). Conclusions: Length of work and age influenced ARI symptoms of workers that exposed to chemicals in artificial nails industry. The strength of the relationship of length of work was greater than age. Keywords: Worker characteristics, worker behaviors, chemicals exposure, ARI symptoms.Â